2021
DOI: 10.1186/s40463-021-00530-0
|View full text |Cite
|
Sign up to set email alerts
|

Rate of malignancy for thyroid nodules with AUS/FLUS cytopathology in a tertiary care center – a retrospective cohort study

Abstract: Background Thyroid nodules are stratified through fine-needle aspiration (FNA) and are often categorized using The Bethesda System for Reporting Thyroid Cytopathology, which estimates the risk of malignancy for six cytopathological categories. The atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS) categories have varying malignancy rates reported in the literature which can range from 6 to 72.9%. Due to this heterogeneity, we assessed the maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(98 reference statements)
1
11
2
Order By: Relevance
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of TBSRTC category III thyroid nodules reported that repeating FNA resulted in a definitive diagnostic entity in 45%-50% of the cases, in which nearly 45% were recategorized into benign category. 10,11 A case series from one institution suggested repeat FNA cytology can help optimize molecular testing for a subset of cytologically indeterminate thyroid nodules. 12 Accordingly, performing Afirma GEC only on nodules with repeat Bethesda III/IV cytology would reduce the rate of surgery for benign nodules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the probable causes of discrepancies between reported results in that respect. Some studies showed a similar frequency of cancers in patients treated surgically after or without rFNA [ 21 , 22 , 23 ]; others indicated an increased rate of malignancy after rFNA, non-significantly [ 8 , 24 , 25 , 26 , 27 , 28 , 29 ] or significantly [ 20 , 30 , 31 , 32 , 33 ] and there are reports that suggested slightly lower malignancy rates in patients undergoing surgery after rFNA in comparison to those treated directly after the diagnosis of category III [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 While patients who have a benign repeat FNA likely have a very low ROM, they still require further monitoring unless their ultrasound is very low suspicion, and surveillance of even those nodules is still an option. 2,9,16 Once a nodule has had 2 benign FNA results, ultrasound surveillance is no longer indicated. Therefore, unless a patient had a very low suspicion ultrasound, at least 2 surveillance points were indicated in our cohort based on these guidelines.…”
Section: Discussionmentioning
confidence: 99%